Lebanon : Report on Performance Under the Program Supported by Emergency Post-Conflict Assistance. (IMF Staff Country Reports; Country Report, 2009)
This report assesses performance of Lebanon Under the Program Supported by Emergency Post-Conflict Assistance (EPCA). The performance has remained broadly favorable, though there has been limited progress on structural reforms. The end-June quantitative target on international reserves was met by a wide margin. Although the primary balance target was also met, the program ceiling on net government financing by the Banque du Liban (BdL) was missed. The BdL has adopted formal policies for the selection, appointment, and rotation of the BdL's external auditors.